2021
DOI: 10.11591/ijere.v10i4.21821
|View full text |Cite
|
Sign up to set email alerts
|

Students’ use behavior towards e-learning tools during COVID-19 pandemics: Case study of higher educational institutions of Thailand

Abstract: <p><span>The research purpose was to conduct an empirical investigation into students’ use behavior of e-learning tools during the COVID-19 pandemic, a case study of higher educational institutions in Thailand. The study applied the UTAUT2 theoretical model. Primary data was collected using a structured questionnaire from a total of 1,493 students across institutions of higher learning in Thailand. Structural equation modelling (SEM) was conducted using AMOS. The findings indicated that student’s b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…More specifically, PE significantly affected university students’ BI to use eLearning platforms meaning that using eLearning platforms will enable students to perform better in their studies. This finding is in agreement with many studies worldwide; Prasetyo et al ( 2021 ) in the Philippines; Muangmee et al ( 2021 ) in Thailand; Raza et al ( 2021 ) in Pakistan; Fouad Altameemi and Abdula Fatah Al-Slehat (2021), Abbad ( 2021 ), Dajani and Abu Hegleh ( 2019 ), in Jordan; Hassan ( 2021 ) in Egypt; Akbar ( 2021 ) in Bahrain; Buabeng-Andoh and Baah ( 2020 ) in Ghana; Tarhini et al ( 2017 ), in England; El-Masri and Tarhini ( 2017 ), in Qatar and the USA; Ain et al ( 2016 ) in Malaysia.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…More specifically, PE significantly affected university students’ BI to use eLearning platforms meaning that using eLearning platforms will enable students to perform better in their studies. This finding is in agreement with many studies worldwide; Prasetyo et al ( 2021 ) in the Philippines; Muangmee et al ( 2021 ) in Thailand; Raza et al ( 2021 ) in Pakistan; Fouad Altameemi and Abdula Fatah Al-Slehat (2021), Abbad ( 2021 ), Dajani and Abu Hegleh ( 2019 ), in Jordan; Hassan ( 2021 ) in Egypt; Akbar ( 2021 ) in Bahrain; Buabeng-Andoh and Baah ( 2020 ) in Ghana; Tarhini et al ( 2017 ), in England; El-Masri and Tarhini ( 2017 ), in Qatar and the USA; Ain et al ( 2016 ) in Malaysia.…”
Section: Discussionsupporting
confidence: 94%
“…Some studies used the UTAUT model to investigate the factors that impact on university students' acceptance of e-learning in the context of the COVID-19 pandemic (e.g., Hassan, 2021 ; Muangmee et al, 2021 ; Prasetyo et al, 2021 ; Raman & Thannimalai, 2021 ; Raza et al, 2021 ), and their results revealed strong links of specific UTAUT constructs to BI of e-learning, as well as between BI and students' usage behavior of e-learning. These recent studies (published in 2020 and 2021) are initially discussed, followed by indicative studies conducted before the pandemic, while studies in the Greek context are reported at the end of this section.…”
Section: Literature Review: Research Related To University Students’ ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It significantly makes a clear view that students have enhanced access to learning information and modern technologies. The increasing possibilities of access to useful information are obvious due to the current ICT development [ 20 24 ]. Additionally, it is mandatory to promote Education 4.0 to the current generation students in classroom lectures.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, MOOCs programs were used as open educational resources (OER) and were not designed to offer academic credits. However, with the advent of the coronavirus pandemic and the need for social distancing, many learning institutions have taken up the idea to offer educational programs in public schools and undergraduate degree programs [ 4 , 5 ]. The MOOCs have a different approach from the previous online learning programs as it is free and available for anyone to enroll.…”
Section: Introductionmentioning
confidence: 99%